The Construction of Forgetfulness: Media Framing as an Instrument to Erase Traces of Human Rights Violations in Prabowo Subianto's Image - Meilandi, Muhammad Rafiq (Jurnal Dakwah dan Komunikasi, 2025)
This study discusses how mainstream media constructs Prabowo Subianto's image through a systematic framing strategy, especially in the context of his track record of past human rights violations and the transformation of his political image since 2014. The main focus of this study is directed at how history is reconstructed through media coverage to fo rm the public's collective memory of image Prabowo Subianto, who now occupies an important position in national politics. Using a qualitative approach through literature study, this study combines the theories of Framing (Entman), Social Construction (Berger & Luckmann), and Collective Memory (Halbwachs & Ricoeur) to analyze the dynamics of the media in shaping public perceptions related to the chosen focus of the problem. The results of this study show that mass media has a central role in reconstructing Prabowo Subianto's image. This process takes place through mainstream media framing strategies that consistently simplify, obscure, and even divert the dark past narrative, while establishing a new persona that suits the needs of contemporary Indonesian politics.